A new LVRT strategy for DGs with different droop gains in islanded microgrid with various loads. Issue 3 (3rd July 2018) - Rajamand, Sahbasadat; Ketabi, Abbas; Zahedi, Abdulhamid
ABSTRACT: The Low Voltage Ride Through (LVRT) is an important requirement in fault conditions for any power system specially microgrids. When the fault occurs, the overcurrent and unbalanced voltage are yielded and these result in serious damages in inverter-based Distributed Generators (DGs) in the microgrid. To prevent this phenomenon, many types of research have been guided to limit the current in faulty conditions and to improve and balance the PCC voltage to be without any distortions. In this paper in islanded mode with reactive power injection during the fault occurrence, the LVRT method is proposed. This reactive power is injected to compensate the voltage dip and simultaneously limit the overcurrents in faulty phases. Also using this method, the faultless phases are not degraded and have no overvoltages. It is noticeable that two inverters in this paper assumed with varying droop gains and so the current and power of them must be divided relative to their droop gains both in faulty and faultless conditions. The simulation results are based on MATLAB Simulink which shows the system improvement in faulty conditions using this method.